2009
DOI: 10.1164/rccm.200905-0795oc
|View full text |Cite
|
Sign up to set email alerts
|

Short-Course Therapy with Daily Rifapentine in a Murine Model of Latent Tuberculosis Infection

Abstract: Rationale: Regimens recommended to treat latent tuberculosis infection (LTBI) are 3 to 9 months long. A 2-month rifampin1 pyrazinamide regimen is no longer recommended. Shorter regimens are highly desirable. Because substituting rifapentine for rifampin in the standard regimen for active tuberculosis halves the treatment duration needed to prevent relapse in mice, we hypothesized daily rifapentine-based regimens could shorten LTBI treatment to 2 months or less. Objectives: To improve an existing model of LTBI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 41 publications
6
74
0
Order By: Relevance
“…A previously described paucibacillary model of latent tuberculosis infection in which BALB/c mice are immunized with the Mycobacterium bovis bacillus Calmette-Guérin (BCG) vaccine (Pasteur strain) (24) was used, with the BCG being a recombinant strain that overexpresses the 30-kDa major secretory protein (rBCG30) (25) and with minor modifications to the model (26). Quantitative cultures of lung homogenates were performed in parallel on selective agar plates (7H11 supplemented with 10% OADC), with 2-thiophenecarboxylic acid hydrazide (TCH) (40 g/ml; Sigma, St. Louis, MO) used to select for M. tuberculosis or hygromycin (40 g/ml; Roche Diagnostics, Indianapolis, IN) to select for rBCG30.…”
Section: Methodsmentioning
confidence: 99%
“…A previously described paucibacillary model of latent tuberculosis infection in which BALB/c mice are immunized with the Mycobacterium bovis bacillus Calmette-Guérin (BCG) vaccine (Pasteur strain) (24) was used, with the BCG being a recombinant strain that overexpresses the 30-kDa major secretory protein (rBCG30) (25) and with minor modifications to the model (26). Quantitative cultures of lung homogenates were performed in parallel on selective agar plates (7H11 supplemented with 10% OADC), with 2-thiophenecarboxylic acid hydrazide (TCH) (40 g/ml; Sigma, St. Louis, MO) used to select for M. tuberculosis or hygromycin (40 g/ml; Roche Diagnostics, Indianapolis, IN) to select for rBCG30.…”
Section: Methodsmentioning
confidence: 99%
“…In this model, mice are immunized with a recombinant BCG strain overexpressing the 30-kDa major secretory protein (76) via the aerosol route and challenged 6 weeks later with virulent M. tuberculosis (77,78), leading to a stable lung census of ϳ10 4 bacilli, which approximates the bacillary burden in human LTBI (38). Perhaps most importantly, this paucibacillary model accurately recapitulates the hierarchy of sterilizing activities of the various drug regimens used to treat human LTBI (78). Recently, this model has been enhanced by the use of C3Heb/FeJ mice, which develop necrotic lung granulomas, and infection may be reactivated by TNF-␣ neutralization (362).…”
Section: In Vivo Models Of M Tuberculosis Growth Restriction and Antmentioning
confidence: 99%
“…However, the relapse rate among patients in some patient populations treated with such an intermittent RFP regimen is unacceptably high, indicating that the optimal dosing regimen of RFP for TB treatment has yet to be fully characterized. Recent studies in a well-validated mouse model of TB disease have shown that the replacement of rifampin with RFP can shorten the treatment duration to 3 months or less when RFP is given daily and that RFP's treatment-shortening activity is dose dependent (4,5). Daily dosing of RFP was well tolerated at doses ranging from 5 to 20 mg/kg of body weight in healthy volunteers (6).…”
mentioning
confidence: 99%